Micro transport phenomena during boiling with 210 figures - Peng, Xiaofeng; SpringerLink (Online service). (New York Springer, 2010)
Micro Transport Phenomena During Boiling? reviews the new achievements and contributions in recent investigations at microscale. The content mainly includes (i) fundamentals for conducting investigations of micro boiling, (ii) microscale boiling and transport phenomena, (iii) boiling characteristics at microscale, (iv) some important applications of micro boiling transport phenomena. This book is intended for researchers and engineers in the field of micro energy systems, electronic cooling, and thermal management in various compact devices/systems at high heat removal and/or heat dissipation. Dr. Xiaofeng Peng, who had passed away on Sep. 10, 2009, was a professor at the Department of Thermal Engineering, Tsinghua University, China.
Summary.
Introduction -- Thermal Physical Fundamentals -- Nucleation Theory -- Jet Flows -- Bubble Dynamics -- Boiling in Microchannel -- Boiling in Droplets -- Boiling in Micro-Structures and Porous Media -- Explosion Boiling -- Some Special Topics.-.
Electronic reproduction.
Keywords: Ebullition; Electronic books